PARTISIPASI MASYARAKAT DALAM MENINGKATKAN PENDIDIKAN DI LEMBAGA PENDIDIKAN ANAK USIA DINI (PAUD) - Shinta HAD Yusup (IKIP Siliwangi, 2018)
The lack of human resources and government socialization of the community in the area related to Early Childhood Education are feared to have an impact on the level of community participation in Early Childhood Education, whereas that will be able to form quality children; children grow according to the stages so they will be ready to enter further education. This study aims to determine community participation and supporting and inhibiting factors in the implementation of the PAUD Al-Furqon program in Weninggalih Sindangkerta Village. The method that I use in this research is Descriptive Analysis Method with qualitative approach. The results of this study indicate that the public participation in Early Childhood Education shows quite encouraging levels. This was driven by a high understanding of the importance of implementing early education. Their participations are shown in the form of friendship with PAUD Al Furqon actively, liaison with PAUD institutions and home, being a supporter of Al Furqon PAUD, actively involved with educators and PAUD managers and supporters of educational goals, as well as beneficiaries of education. Other forms include being a motivator for parents, contributing various resources, and participating in improving the quality of PAUD Al Furqon.